A Journey into the Dark Depths of One´S Own Mind, Or "I Am Their God" by Josef PaNek - Merenus, Ales (Bohemica Olomucensia, 2024)
The study "A journey into the dark depths of one's own mind, or I am their God by Josef Panek" brings an analysis of Josef Panek's latest prose entitled I am their God and it also engages in the evaluation of the critical reception of this book. It interprets the basic semantic lines of the work and shows Panek's typical narrative strategies. However, it is devoted above all to the fictional consciousness of the main character, which represents the central space and the focus of the meaning of the entire text. In the final part, the study attempts to critically assess Panek's novel and to explain why this prose did not fulfill the expectations that his previous book, Love in the Age of Global Climate Change, aroused in his readers.
Keywords: Josef Panek; contemporary Czech prose; culture shock; I am their god; fictional mind